Implementation Of Profit Sharing System In Cattle Farming Business Reviewed From The Perspective Of Matter (Case Study Of Siarang-Arang Plantation Village) - Irsan Al Fadhil Nasution; Tri Inda Fadhila Rahma; Ahmad Muhaisin (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
The profit sharing system is a cooperation agreement between the capital owner and the capital manager, where the profit is divided according to the agreement. In the Siarang-arang plantation village, the practice of mudharabah is still carried out verbally and based on trust without a written agreement, which has the potential to cause usury and gharar. Therefore, this study aims to analyze how the profit sharing system is applied by cattle farms and whether it is in accordance with Islamic principles. In this study using qualitative research with collection techniques in the form of observation and interviews. So the results of this study that the Siarang-arang plantation village has implemented a profit-sharing system with a mudharabah contract that is in accordance with the basic principles of Islamic sharia. This strengthens both between the actors of the contract and maintains harmony between the local community.